The Urgency of Reforming the Criminal Justice System Through Penal Mediation as Part of the Humanity Approach in the Conceptual Framework of Restorative Justice - Tio, Guruh Tio Ibipurwo (Jurnal Hukum Respublica, 2023)
The settlement of criminal cases through the concept of restorative justice in the criminal justice system can be a way out of the gap in justice for victims and perpetrators. Victims are positioned as those who suffer losses and are often in a disadvantageous position. Meanwhile, perpetrators with state intervention receive retribution in the form of suffering for their crimes, giving rise to a stigma that the perpetrator is a bad person who deserves to be punished severely. Restorative justice as a way out of the justice gap is faced with the non-uniformity of the laws and regulations that regulate it so that it is vulnerable to causing unequal treatment of the parties in its application. Criminal mediation is part of the concept of restorative justice, which is expected to provide a balance of justice for the parties and the community so that they can realize the overall goal of punishment, namely the protection and welfare of the community (social defense and social welfare) as part of the humanist approach. The research method used in this research is normative juridical with a conceptual approach and the approach to legislation using primary and secondary legal materials.